Distinctive Features of the Classification of Secular and Islamic Sciences in Eastern and Western Philosophy - Safarov Maqsudali Kamol ogli (Pubmedia Social Sciences and Humanities, 2026)
This research explores the potential and strategic directions for transitioning Uzbekistan toward a green economy, focusing on renewable energy integration and sustainable development. The study uses a policy-review approach, analyzing current environmental strategies, energy consumption trends, and the feasibility of alternative energy sources like solar and wind power in the region. The findings indicate that Uzbekistan has significant natural potential for renewable energy. The transition has begun with industrial decarbonization and the promotion of energy-efficient technologies, but requires more robust financial incentives. Adopting a green economy model is essential for Uzbekistan's long-term environmental and economic stability. Success depends on the integration of innovative technologies and the alignment of economic policies with international environmental standards.